An ex vivo Tissue Culture Model for the Assessment of Individualized Drug Responses in Prostate and Bladder Cancer - van de Merbel, Arjanneke F.; van der Horst, Geertje; van der Mark, Maaike H.; van Uhm, Janneke I. M.; van Gennep, Erik J.; Kloen, Peter; Beimers, Lijkele; Pelger, Rob C. M.; van der Pluijm, Gabri (Frontiers in Oncology, 2018)
Urological malignancies, including prostate and bladder carcinoma, represent a major clinical problem due to the frequent occurrence of therapy resistance and the formation of incurable distant metastases. As a result, there is an urgent need for versatile and predictive disease models for the assessment of the individualized drug response in urological malignancies. Compound testing on ex vivo cultured patient-derived tumor tissues could represent a promising approach. In this study, we have optimized an ex vivo culture system of explanted human prostate and bladder tumors derived from clinical specimens and human cancer cell lines xenografted in mice. The explanted and cultured tumor slices remained viable and tissue architecture could be maintained for up to 10 days of culture. Treatment of ex vivo cultured human prostate and bladder cancer tissues with docetaxel and gemcitabine, respectively, resulted in a dose-dependent anti-tumor response. The dose-dependent decrease in tumor cells upon administration of the chemotherapeutic agents was preceded by an induction of apoptosis. The implementation and optimization of the tissue slice technology may facilitate the assessment of anti-tumor efficacies of existing and candidate pharmacological agents in the complex multicellular neoplastic tissues from prostate and bladder cancer patients. Our model represents a versatile ‘near-patient’ tool to determine tumor-targeted and/or stroma-mediated anti-neoplastic responses, thus contributing to the field of personalized therapeutics